Handling Domestic Violence Through Mediation Out of Court - Muhammad Mahson; Sri Kusriyah; Rakhmat Bowo Suharto (Law Development Journal, 2022)
This study was structured to determine the settlement of cases of domestic violence in the city of Pekalongan. This aims to determine the approach to mediation outside the court in the settlement of domestic violence as an alternative. It also analyzes the obstacles in solving cases and their solutions. Method The approach in this study is a qualitative research that produces descriptive data in the form of written or spoken words from people and observable behavior. The specification of this research is descriptive qualitative which analyzes and presents facts systematically to determine the psychological condition of women and children victims of domestic violence. This study concludes that domestic violence in the city of Pekalongan is more experienced by women who are a wife, while the perpetrators are dominated by men who are husbands. Settlement according to state law regulated in the Law on the Elimination of Domestic Violence, it is necessary to find an alternative solution. The settlement through out-of-court mediation with the Pekalongan City Women, Children and Youth Protection Institute (LP PAR) as a companion is an alternative solution as an effort to restore good name, and dignity, especially for women as victims.